Application of Artificial Intelligence [AI] for Automated Essay Grading in Nigerian Schools - Muhammad Auwal Yakubu; Zohaib Hassan Sain; Uthman Shehu Lawal; Septian Arief Budiman (Indonesian Journal on Education (IJoEd), 2024)
This paper explores the potential application of Artificial Intelligence (AI) for automated essay grading in Nigerian schools. Building on the current challenges in the Nigerian education system, including large student populations, time constraints, and inconsistent grading standards. The paper analyses how AI-based automated essay grading systems can address these issues by improving the assessment process's efficiency, consistency, and scalability. It also provide an overview of AI-based grading mechanisms, including machine learning and natural language processing techniques. It analyzes global case studies from countries like the United States, China, Japan, Spain, and Germany to draw insights into successful implementation strategies. The study also examines emerging applications of AI essay grading in African contexts, including South Africa, Kenya, and Egypt. Key findings highlight the potential benefits of AI grading systems in Nigerian schools, including reduced grading time, increased objectivity, and more detailed student feedback. However, the paper also identifies significant challenges like infrastructure deficits, technical limitations, ethical concerns, and cost implications. Thus, concludes with recommendations for implementing AI essay grading in Nigerian schools, proposing a gradual rollout strategy, developing comprehensive policy frameworks, and collaborating with technology providers. These recommendations aim to address the Nigerian context's unique challenges while leveraging AI's potential to enhance educational assessment and outcomes.